1988
DOI: 10.1192/bjp.152.5.641
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Flow in Chronic Cocaine Users: A Study with Positron Emission Tomography

Abstract: Occurrence of cerebrovascular accidents has been associated with cocaine abuse. We investigated the relative distribution of cerebral blood flow (CBF) in groups of chronic cocaine users, and of normal controls. Relative CBF was measured using positron emission tomography and 15 oxygen-labelled water. The cocaine users showed areas of deranged CBF as evidenced by patchy regions of defective isotope accumulation throughout their brain. The chronic cocaine users showed decreased relative CBF in the prefrontal cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
154
1
7

Year Published

1990
1990
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 344 publications
(181 citation statements)
references
References 39 publications
19
154
1
7
Order By: Relevance
“…Decreased cerebral blood flow, as measured by FDG-PET, selective to the prefrontal cortex has been reported in cocaine users (Volkow et al, 1988a). Similarly, decreased frontal brain glucose metabolism has been found in cocaine dependent subjects at baseline and at 3 months (Volkow et al, 1992).…”
Section: Discussionmentioning
confidence: 78%
“…Decreased cerebral blood flow, as measured by FDG-PET, selective to the prefrontal cortex has been reported in cocaine users (Volkow et al, 1988a). Similarly, decreased frontal brain glucose metabolism has been found in cocaine dependent subjects at baseline and at 3 months (Volkow et al, 1992).…”
Section: Discussionmentioning
confidence: 78%
“…Anatomic studies of cocaine-dependent individuals have identified the following changes in the PFC: reduced gray matter (Franklin et al, 2002;Matochik et al, 2003), decreased white matter integrity (Lim et al, 2002), and increased white matter hyperintensities (Lyoo et al, 2004). Physiologic studies have shown decreased metabolism in the orbitofrontal cortex (Volkow et al, 1988) and increased cerebrovascular resistance in the arteries that supply the PFC (Herning et al, 1999). Some reports of neuropsychological testing in cocaine using subjects have identified decreased performance on tests that require the support of prefrontal structures (Ardila et al, 1991;Berry et al, 1993;Beatty et al, 1995;van Gorp et al, 1999;Di Sclafani et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, to whatever extent delay discounting and substance abuse are causally linked, it is indeterminable from cohort comparisons in which direction the causal arrow points. It is possible, for example, that the effects of chronic drug use on the brain (Volkow et al, 1988, Volkow et al, 1991, London et al, 1990, Kosten, 1998 might affect performance on delay discounting tasks. Or, perhaps the life-style of the addict might dispose her to emphasize immediate attainment of reward (a possibility we will consider further in the context of our discussion of willpower below).…”
Section: Empirical Studies Of Discounting In Addicted Populationsmentioning
confidence: 99%